Produção de cebola sob lâminas de irrigação e níveis de nitrogênio na bacia do rio Poxim - Massaranduba, Wendel de Melo (2020)
The onion (Allium cepa L.) is a vegetable with great expression in the national and international scene due to its versatility in human food, having high importance in the generation of income, mainly for family agriculture. The inadequate use of water and nutrients has generated conflicts and environmental risks, and more efficient and sustainable use is essential. The objective of this work was to evaluate the application of 5 irrigation depths (50, 75, 100, 125 and 150% of the crop evapotranspiration - ETc), in the productivity and quality of onion bulbs, submitted to 4 doses of nitrogen fertilization (40, 80, 120 and 160 kg ha-1 ), totaling 20 treatments and 4 repetitions. The treatments were arranged in randomized blocks and the irrigation blade factor arranged in bands. The application of the depths was carried out with a daily watering shift through a drip irrigation system. After harvest were evaluated: total bulb productivity, commercial bulb productivity, average mass of commercial bulbs, water use efficiency for total bulb productivity, water use efficiency for commercial bulb productivity, pH determination, soluble solids, titratable acidity, soluble solids / titratable acidity and bulb shape ratio. The highest total and commercial productivity were found with the application of the blade estimated at 122% of ETc, 48.95 and 48.36 t ha-1 , respectively. The irrigation depths that promoted greater efficiency in the use of water for total and commercial production were estimated at 74.24 and 86.25% of ETc, respectively. The content of soluble solids was not influenced by the differentiation of water depths and nitrogen doses.